1996
DOI: 10.1590/s0101-81751996000100002
|View full text |Cite
|
Sign up to set email alerts
|

Estimulação da espermiação em curimbatá Prochilodus scrofa (Steindachner) através de aplicaçoes de HCG (Ostheichthyes, Characiformes, Prochilodontidae)

Abstract: Benedicto do E.S. de Campos 3 ABSTRACT. STIMULATION OF SPERMIATlON WITH HORMONAL INJECTIONS lN THE CUR IMBATÁ PROCHILODUS SCROFA (STEINDACIINER) (OSTIIEICIITIIYES, CIIARACIFORMES, PROCIIILODONTIDAE). Sperm of 180 three year old males of curimbatá, Proehilodus serolo (Stei ndachner, 188 1), was collected to verify the possibility of utilization of these males more than one time, and to know how long afier the hormonal induction would occur the highest production of milt. This experiment was carried out in 1991 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Other studies report 90% (KAVAMOTO et al, 1999) and 97% (MILIORINI et al, 2011) normal sperm in Prochilodus lineatus, 64% in Leporinus elongatus (STREIT Jr. et al 2008b), 57% in the dorado Salminus maxillosus (STREIT Jr. et al 2008a), 53% in the cachara Pseudoplatystoma reticulatum (STREIT Jr. et al 2012) and 16% in the Nile tilapia Oreochromis niloticus (MATAVELI et al 2007). The variation of normal semen percentage found among the species is influenced by several factors such as the nutritional status of the fish, size, age, and time of the year (VIVEIROS; GODINHO, 2009;SANCHES et al, 2011;NAVARRO et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Other studies report 90% (KAVAMOTO et al, 1999) and 97% (MILIORINI et al, 2011) normal sperm in Prochilodus lineatus, 64% in Leporinus elongatus (STREIT Jr. et al 2008b), 57% in the dorado Salminus maxillosus (STREIT Jr. et al 2008a), 53% in the cachara Pseudoplatystoma reticulatum (STREIT Jr. et al 2012) and 16% in the Nile tilapia Oreochromis niloticus (MATAVELI et al 2007). The variation of normal semen percentage found among the species is influenced by several factors such as the nutritional status of the fish, size, age, and time of the year (VIVEIROS; GODINHO, 2009;SANCHES et al, 2011;NAVARRO et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Os machos produziram grande volume de sêmen em comparação ao observado por Ferreira et al (2001) Kavamoto et al (1999), estudando sêmen de curimbatá (Prochilodus lineatus), verificaram que 9,54% dos espermatozóides apresentaram alguma alteração morfológica, relacionada à aplicação de hormônios e ao tempo decorrido até a espermiação.…”
Section: Resultsunclassified
“…Kavamoto et al . (1999) found that spermatozoa of Prochilodus lineatus presented abnormalities after being treatment with human chorionic gonadotropin. Moraes et al .…”
Section: Discussionmentioning
confidence: 99%
“…This task includes the evaluation of any morphological abnormalities in spermatozoa. However, studies on sperm morphology in Brazilian native fish have so far been limited (Kavamoto et al ., 1999; Streit Jr et al ., 2008; Murgas et al ., 2011; Maria et al ., 2012). The increase in sperm diseases has led to reduced sperm motility and vigour (Lahnsteiner et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%